Analysis of Cell Dielectrophoretic Properties Using Isomotive Creek-Gap Electrode Device - Shigeru Tada; Noriko Sato (Sensors)
Various types of dielectrophoresis (DEP) cell separation devices using AC electric fields have been proposed and developed. However, its capability is still limited by a lack of quantitative characterization of the relationship between frequency and force. In the present study, this limitation was addressed by developing a method capable of fast and accurate quantification of the dielectric properties of biological cells. A newly designed Creek-gap electrode device can induce constant DEP forces on cells, realizing the isomotive movement of cells suitable for DEP analysis. The real number part of the Clausius–Mossotti (CM) factor of cells, <semantics>Re(β)</semantics>, was obtained by simple cell velocimetry together with the numerical three-dimensional (3D) electric field analysis. Human mammary cells, MCF10A, and its cancer cells, MCF7 and MDAMB231, were used as model cells to evaluate the capability of the proposed device. The estimation of <semantics>Re(β)</semantics> using the Creek-gap electrode device showed good agreement with previously reported values. Furthermore, the thermal behavior of the Creek-gap electrode device, which is crucial to cell viability, was investigated by adopting micro laser-induced fluorescence (LIF) thermometry using Rhodamine B. The temperature rise in the device was found to be approximately several degrees Celsius at most. The results demonstrate that the proposed method could be a powerful tool for fast and accurate noninvasive measurement of the DEP spectrum and the determination of the dielectric properties of biological cells.